Pengaruh Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian melalui Aplikasi Alfagift pada Masyarakat Kecamatan Cisarua Kabupaten Bandung Barat - Nurul Maulani Hasanah; Umi Narimawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid growth of digital retail applications has intensified competition among modern retailers, requiring effective promotional strategies and reliable service quality to influence consumer purchasing decisions. This study aims to analyze the effect of promotion and service quality on purchasing decisions through the Alfagift application among residents of Cisarua District, West Bandung Regency. A quantitative approach with a descriptive–verificative method was employed. Data were collected from 100 Alfagift users using an online questionnaire based on a five-point Likert scale. The data were analyzed using multiple linear regression, supported by t-test, F-test, and coefficient of determination (R²) with SPSS version 27. The results show that promotion has a positive and significant effect on purchasing decisions (t = 2.212; sig. = 0.029). Service quality also has a positive and significant effect and demonstrates a stronger influence on purchasing decisions (t = 4.181; sig. = 0.000). Simultaneously, promotion and service quality significantly affect purchasing decisions (F = 12.212; sig. = 0.000). The coefficient of determination indicates that 20.1% of purchasing decision variation is explained by these variables. The findings highlight that improving service quality, supported by relevant and consistent promotional activities, is essential to strengthen consumer purchasing decisions in digital retail applications.